(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The article focuses on the precautionary principle, a principle that - according to a quite shared definition – requires decision-makers to adopt precautionary measures to prevent environmental or human health hazards, even when scientific evidence is uncertain. After some preliminary remarks on the possible meanings of this principle and its historical roots and development, the article analyses the role of the precautionary principle within the Italian Constitutional case-law. Among the possible uses of the principle by the Court, two are worth studying: the reference to a precautionary approach when fixing conflicts between State and Regions, and the use of the precaution in order to assess the balance between values in the judicial review of legislation.